Local specialists’ experience and skills in animal behaviour studies: insights from wild chimpanzee field assistants - Soldati, Adrian; Fedurek, Pawel; Eleuteri, Vesta; Zuberbühler, Klaus; Call, Josep; Muhumuza, Geresomu; Mbotella, Monday; Adue, Sam; Boscou, Chandia; Asua, Jackson; Lomoro, Dennis; Muhanguzi, Geoffrey; et al. (The royal society publishing, 2026)
The study of wild animal behaviour and cognition has greatly benefited from the foundational work of local specialists (LSs), particularly field assistants. In primate research, long-term studies rely on accurate identification and tracking of individuals-a skill often honed by LSs and passed on to international specialists (ISs). Despite growing recognition in publications, LSs' scientific contributions often remain undervalued. Here, we show that LSs at the Budongo Conservation Field Station (Uganda) reliably extract acoustic information (caller identity, sex and age, call components and production context) from long-distance pant hoot calls produced by wild chimpanzees. Importantly, LSs significantly outperform ISs at identifying individuals (LS accuracy = 50% (95% confidence interval (CI): 45-56%); IS accuracy = 8% (95% CI: 5-11%)), an important skill for recognizing and locating individuals in dense forests. LSs' performance was positively associated with duration of working experience. Given the limited field time of ISs (typically 1-2 years), LSs' expertise and longer commitment (mean 16.75 years) represent an essential yet underacknowledged scientific resource. Our study highlights LSs' critical role in ethological research-not only enhancing skills and data quality, but also potentially helping address both ethical (e.g. community involvement) and environmental (e.g. travel carbon footprint) challenges linked to fieldwork in remote locations. MEDLINE
Keywords: local specialists; helicopter science; animal communication; acoustic information; primatology; chimpanzee pant hoots